2010
DOI: 10.1103/physrevlett.104.037203
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement in Supramolecular Spin Systems of Two Weakly Coupled Antiferromagnetic Rings (Purple-Cr7Ni)

Abstract: We characterize supramolecular magnetic structures, consisting of two weakly coupled antiferromagnetic rings, by low-temperature specific heat, susceptibility, magnetization and electron paramagnetic resonance measurements. Intra- and inter-ring interactions are modeled through a microscopic spin-Hamiltonian approach that reproduces all the experimental data quantitatively and legitimates the use of an effective two-qubit picture. Spin entanglement between the rings is experimentally demonstrated through magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 23 publications
(23 reference statements)
2
98
0
Order By: Relevance
“…The possibility to extract all two-spin dynamical correlation functions opens remarkable perspectives in the understanding of crucial but elusive quantum phenomena in several classes of magnetic molecules. In particular, supramolecular complexes containing linked molecular nanomagnets have been demonstrated to display entanglement [12,13] and to be excellent candidates for implementing quantumcomputation [8] and quantum-simulation algorithms [9]. The present method could be applied to reach a profound knowledge of the structure of the eigenstates of these complexes and of the entanglement between different molecular qubits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility to extract all two-spin dynamical correlation functions opens remarkable perspectives in the understanding of crucial but elusive quantum phenomena in several classes of magnetic molecules. In particular, supramolecular complexes containing linked molecular nanomagnets have been demonstrated to display entanglement [12,13] and to be excellent candidates for implementing quantumcomputation [8] and quantum-simulation algorithms [9]. The present method could be applied to reach a profound knowledge of the structure of the eigenstates of these complexes and of the entanglement between different molecular qubits.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most studied MNMs both for its intrinsic interest and for being the precursor of a large family of heterometallic molecules and supramolecular complexes which are intensively studied for a number of fundamental and applicative issues [8,12,13,[26][27][28]. The spin-Hamiltonian of Cr 8 contains a dominating nearest-neighbor Heisenberg AF exchange and small axial anisotropic terms:…”
Section: The Cr8 Prototype Antiferromagnetic Ringmentioning
confidence: 99%
See 1 more Smart Citation
“…Spin entanglement can be obtained within a single molecule or at supramolecular level (i.e., between molecules) by controlling spin topology and magnetic interactions. Along this line, dimers of molecular spins with weak permanent magnetic coupling could be designed and synthesized [25] and sizable spin entanglement was demonstrated [26]. One issue of this approach is related to the fact that, during the gate operation, the coupling between the two qubits needs to be switched on and off in order to allow independent rotation of the two spin qubits.…”
Section: Coherent Spin Dynamics Of Spin Ensemblesmentioning
confidence: 99%
“…7,8 In addition, MNMs exhibit a wide range of intriguing quantum phenomena, such as quantum tunneling of the magnetization, [9][10][11] decoherence, 12,13 or quantum entanglement between distinct cores. [14][15][16][17] MNMs also present great advantages from the standpoint of theoretical modeling. Indeed, it has been demonstrated that the effective spin Hamiltonian is a powerful model to describe magnetic properties of these clusters.…”
Section: Introductionmentioning
confidence: 99%